(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
This “essay at the dark” brings philosophical and artistic reflections on the dark and shadow as axes of creation, and not light in the foreground as commonly occurs. We revisited our writings from years ago and, like someone groping an unknown space, we elaborated personal reflections on creative processes, quotes and images about why we consider the dark as the protagonist of our works. As light designer and shadow puppeteers, our research dialogues directly with our artistic practices and here, as in a creative memorial, we record our perspectives as in a written dialogue, seeking to register common paths and issues yet to be explored.